Optimization of a technology‐supported physical activity promotion intervention for breast cancer survivors: Results from Fit2Thrive. Issue 5 (23rd November 2021) - Phillips, Siobhan M.; Penedo, Frank J.; Collins, Linda M.; Solk, Payton; Siddique, Juned; Song, Jing; Cella, David; Courneya, Kerry S.; Ackermann, Ronald T.; Welch, Whitney A.; Auster‐Gussman, Lisa A.; Whitaker, Madelyn; et al.
Abstract : Background: The benefits of moderate to vigorous physical activity (MVPA) for breast cancer survivors are well established. However, most are insufficiently active. Fit2Thrive used the Multiphase Optimization Strategy methodology to determine the effect of 5 intervention components on MVPA in this population. Methods: Two hundred sixty‐nine participants (mean age, 52.5 years; SD, 9.9 years) received a core intervention (the Fit2Thrive self‐monitoring app and Fitbit) and were randomly assigned to 5 intervention components set to on/off in a full factorial experiment: support calls, deluxe app, buddy, online gym, and text messages. The intervention was delivered over 12 weeks with a 12‐week follow‐up. MVPA was measured via accelerometry at the baseline (T1), at 12 weeks (T2), and at 24 weeks (T3). The main effects and interaction effects at each time point were examined for all components. Results: Trial retention was high: 91.8% had valid accelerometer data at T2 or T3. Across all conditions, there were significant increases in MVPA (+53.6 min/wk; P < .001) and in the proportion of survivors meeting MVPA guidelines (+22.3%; P < .001) at T2 that were maintained but attenuated at T3 (MVPA, +24.6 min/wk; P < .001; meeting guidelines, +12.6%; P < .001). No individual components significantly improved MVPA, although increases were greater for the on level versus the off level for support calls, buddy, and text messages at T2 and T3. Conclusions: The Fit2Thrive core intervention (the self‐monitoring app and Fitbit) is promising for increasing MVPA in breast cancer survivors, but the components provided no additional increases in MVPA. Future research should evaluate the core intervention in a randomized trial and determine what components optimize MVPA behaviors in breast cancer survivors. Abstract : Systematically testing 5 technology‐supported physical activity promotion intervention components alongside the Fit2Thrive core intervention (Fit2Thrive self‐monitoring app and Fitbit) results in an increase in physical activity after the intervention and at a 12‐week follow‐up in breast cancer survivors. However, increases are not significantly greater with any component turned on versus off. This indicates that the Fit2Thrive core is a promising scalable strategy for increasing moderate to vigorous physical activity.